STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN DAN LEVERAGE - FAIZA MUKLIS (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
The research theme is the financial and banking institutions. The purpose of this study is to empirically tests the association between ownership structure, firm size and leverage on earnings management in Indonesian listed company. Using a correlation method with observation from 2012 to 2013 foods and beverages firms we try to model the relationship between earnings management and these variables. Ownership concentration was used as proxy for ownership structure, total assets as a measure firm size, and discretionary accruals for earnings management. Modified Jones Model was used for calculation of discretionary accruals. The results indicate a significant negative relation between leverage and earning management. Hovever, ownership concentration and firm size were not significant. This findings suggest that there is a beneficial consequence of debt because the increased debt might reduce manager’s discretionary spending, and in turn, reduces accrual earnings management.